Correlation between body mass index with musculoskeletal disorders in employees at Annika Linden Center - I Gusti Ayu Sri Novianti; I. A. Pascha Paramurthi; Komang Tri Adi Suparwati; Dewa Ayu Agustini (Physical Therapy Journal of Indonesia, 2023)
Background: Problems that often occur in employees are health problems, especially musculoskeletal complaints. Internal and external factors can cause musculoskeletal complaints in employees. One of the internal factors is body mass index (BMI). Someone with an obese BMI will increase the risk of musculoskeletal disorders because when they want to work, the pressure on the waist usually feels heavy due to weakened muscle tone. This study aims to determine the relationship between BMI with musculoskeletal disorders (MSDs). Methods: This study used a cross-sectional study design. The sampling technique in this study uses the total sampling method. The number of samples is 50 people. Researchers took place at the Annika Linden Center. The measurement of musculoskeletal disorders using the Nordic body map (NBM). Results: The analysis of the relationship between BMI and musculoskeletal disorders using the Somers test obtained p=0.001 (p<0.05), meaning a significant relationship exists between body mass index and musculoskeletal disorders. Conclusion: There is a significant relationship between BMI and musculoskeletal complaints in Annika Linden Center employees.